Enhancing magnetic vacancies in semiconductors by strain - Kan, Erjun (2013)
Although cation-vacancies can induce localized magnetic moments in semiconductors, the collective magnetism is impeded by low vacancy concentration. To improve the vacancy concentration, we study the effect of external hydrostatic strain on the vacancy formation energy. Our first-principles calculations discover that vacancy formation energy is significantly reduced in ionic semiconductors with the monotonic volume contraction, while only slightly decreased in covalent semiconductors. Especially for ZnO, the equilibrium concentration of cation-vacancies has been improved by 109 times. We predicted that strain can be used to produce “d0 magnetism” in ionic semiconductors much easier in experiments.